Managing laryngotracheal trauma: 3 year experience at a tertiary hospital in North India - Munjal, Manish; Kaur, Japneet; Rishi, Porshia; Singh, Harjinder; Tuli, Nitika; Munjal, Shubham (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Laryngotracheal trauma includes life threatening injuries that are encountered by emergency care physicians, trauma surgeons and ENT surgeons. These injuries can occur in the most remote areas or in the busiest metropolitan setting. Earlier intervention is vital in order to reduce the mortality and morbidity associated with insult to the aerodigestive tract and surrounding structures. Methods: This is a retrospective study of 21 patients who presented to the emergency department of Dayanand Medical College and Hospital, Ludhiana, for management of injuries to aerodigestive tract over a period of 3 years from January 2016 to December 2019. Results: Twenty-one patients were seen with acute injuries to the airway in the emergency department. There were 12 males and 9 female patients out of which there were 10 men and 5 women, 3 girls and 2 boys ranging in age from 9 to 60 years. Although most of these injuries occurred as a result of blunt trauma, 6 were due to penetrating injuries out of which 2 were due to homicidal assault. Stridor was the most common finding followed by surgical emphysema. Twelve patients were in acute respiratory distress requiring emergency procedures to secure the airway. All patients underwent successful repair of the injuries. All patients except 1 had a good airway. Conclusions: Laryngotracheal injury is rare but very crucial and life-threatening surgical emergency. Timely intervention is crucial in the management of laryngotracheal trauma in order to prevent complications.